Examining Whether Onfield Motor Incoordination Is Associated With Worse Performance on the SCAT5 and Slower Clinical Recovery Following Concussion - Iverson, Grant L.; Van Patten, Ryan; Gardner, Andrew J. (Frontiers in Neurology, 2021)
Objective: To examine the relationship between video-identified onfield motor incoordination, the acute assessment of concussion, and recovery time during three seasons of National Rugby League (NRL) play. Methods: Blows to the head (“head impact events”) were recorded by sideline video operators and medical staff. Any player with a suspected concussion underwent a Head Injury Assessment in which he was taken off the field and medically evaluated, including the administration of the Sports Concussion Assessment Tool, 5th Edition (SCAT5). Video footage was later examined to determine the presence or absence of onfield motor incoordination following the head impact event. Results: Motor incoordination was identified in 100/1,706 head injury events (5.9%); 65 of the 100 instances of motor incoordination (65.0%) were ultimately medically diagnosed with a concussion. In 646 athletes for whom SCAT5 data were available, those with motor incoordination were more likely to report both dizziness and balance problems than those without motor incoordination, but there were no group differences on an objective balance test. Additionally, there was no relationship between presence/absence of motor incoordination and number of games missed or time to medical clearance for match play. Conclusion: In NRL players, motor incoordination is a readily observable onfield sign that is strongly associated with a medical diagnosis of concussion and with self-reported dizziness/balance problems. However, onfield motor incoordination is not associated with objective balance performance and it is not predictive of time to recover following concussion.